2015
DOI: 10.1261/rna.046367.114
|View full text |Cite
|
Sign up to set email alerts
|

The Ll.LtrB intron from Lactococcus lactis excises as circles in vivo: insights into the group II intron circularization pathway

Abstract: Group II introns are large ribozymes that require the assistance of intron-encoded or free-standing maturases to splice from their premRNAs in vivo. They mainly splice through the classical branching pathway, being released as RNA lariats. However, group II introns can also splice through secondary pathways like hydrolysis and circularization leading to the release of linear and circular introns, respectively. Here, we assessed in vivo splicing of various constructs of the Ll.LtrB group II intron from the Gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 36 publications
5
58
0
Order By: Relevance
“…We observed a third productive splicing pathway in the case of trans-splicing nad5 intron 2, one that is analogous to the cis-splicing group II intron pathway which generates a full-length in vivo circularized intron (Murray et al, 2001;Monat et al, 2015). However in the present case, there is a short stretch of non-encoded nucleotides at the junction between the intron 5′ and 3′ ends, and to our knowledge this is the first such report for a trans-splicing intron.…”
Section: Discussionsupporting
confidence: 46%
“…We observed a third productive splicing pathway in the case of trans-splicing nad5 intron 2, one that is analogous to the cis-splicing group II intron pathway which generates a full-length in vivo circularized intron (Murray et al, 2001;Monat et al, 2015). However in the present case, there is a short stretch of non-encoded nucleotides at the junction between the intron 5′ and 3′ ends, and to our knowledge this is the first such report for a trans-splicing intron.…”
Section: Discussionsupporting
confidence: 46%
“…CircRNAs are produced by circularization of a single exon 9 , 10 , several exons 11 , exons and introns named exon-intron circRNA (ElcirRNA) 12 , or intronic sequences alone (circularized intron RNA; ciRNA) 13 , 14 . CircRNAs were first found in some plant viroids as covalently closed circular RNA molecules with the base pairing between inverted complementary sequences at the 3' and 5' ends of linear molecules 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial description of the branching ( 14 – 16 ) and the hydrolysis pathways ( 17 , 18 ), circularization of group II introns was mostly overlooked. Nevertheless, since that time, group II intron RNA circles from various systems were described both in vivo ( 19 23 ) and in vitro ( 11 , 24 ). We recently demonstrated that a significant proportion of the model group II intron, Ll.LtrB, from the Gram-positive bacterium Lactococcus lactis , excises as circles in vivo ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, since that time, group II intron RNA circles from various systems were described both in vivo ( 19 23 ) and in vitro ( 11 , 24 ). We recently demonstrated that a significant proportion of the model group II intron, Ll.LtrB, from the Gram-positive bacterium Lactococcus lactis , excises as circles in vivo ( 19 ). Interestingly, we detected intron circles for all the Ll.LtrB mutants studied and demonstrated that both branching and circularization take place concurrently in vivo .…”
Section: Introductionmentioning
confidence: 99%